Patterning of Nano and Micromaterials on Polymer Substrates Using Spraying, Selective Laser Treatment, and Adhesive Delamination for Sensing Applications - Mehraneh Tavakkoli Gilavan; Oluwawemimo Igun; Md Ali Akbar; Shayan Jahangirifard; Peter Kruse; Ponnambalam Ravi Selvaganapathy (Advanced Materials Interfaces)
Abstract Integrating conductive nanomaterials with polymer substrates in a scalable and low‐cost way is crucial for developing flexible electronics. This work presents a scalable process for integrating high‐quality nanomaterials with polymer films to fabricate flexible electrical devices by combining simple yet effective techniques. Various conductive patterns on polymer substrates are successfully created by utilizing a combination of nanomaterial spraying, laser treatment, and adhesive delamination. The laser treatment embeds the sprayed nanoparticles onto the polymer surface by partially melting the polymer and significantly enhancing their adhesion selectively in places where it traces a path. This method incorporates single‐walled carbon nanotubes, graphene, and molybdenum disulfide onto polymers such as polypropylene, polyvinylidene fluoride, and nylon, achieving a minimum line width of 350 µm. The versatility of this technique is demonstrated by fabricating a range of devices, including microheaters, temperature sensors, chemiresistive sensors, and electrochemical sensors. The fabricated devices exhibit excellent durability and stable performance, addressing the limitations of integrating nanomaterials into polymer films. Additionally, this method allows for precise control of conductivity and pattern complexity, making it suitable for various applications. This work contributes to the advancement of flexible electronics, providing a scalable and adaptable method for creating high‐performance devices.